Biogenesis and homeostasis of mast cell lysosome related secretory granules - Sagi-Eisenberg, Ronit (Frontiers in Cell and Developmental Biology, 2025)
Mast cells (MCs) are sentinel cells of the immune system that play important protective roles in innate host defenses but are also key effectors of allergic responses and chronic inflammatory diseases. Both physiological and pathophysiological responses of MCs are mediated by the release of inflammatory mediators, many of which are stored, preformed, in secretory granules (SGs), and released by regulated exocytosis in response to multiple stimuli. MC SGs belong to the family of lysosome related organelles (LROs), as indicated by their content of lysosomal hydrolases, lysosomal membrane proteins and acidic pH. The SGs derive from the Golgi and increase in size in a quantal manner by their fusion with additional SGs. They have access to external cargo, which they acquire by fusion with endosomes and contain LC3, which they acquire by fusion with amphisomes. This review discusses the underlying mechanisms of MC SG biogenesis and remodeling.